ANALISIS KRITIK PEMBUKTIAN ELEKTRONIK DALAM HUKUM ACARA PERDATA : TANTANGAN DAN PROSPEK DI ERA DIGITAL - Lubis, Dr.Fauziah; Ramadhani Purba, Sofia (Cattleya Darmaya Fortuna, 2024)
Numerous parts of life have encountered huge change because of the advancement of data and correspondence innovation (ICT), including the lawful calling. One of the significant effects of ICT is the introduction of electronic evidence as a new type of evidence in civil procedural law. Electronic proof offers various advantages, like simplicity of passage, stockpiling, and scattering. Notwithstanding, then again, electronic proof likewise raises different troubles, like approval, dependability and security. The purpose of this study is to investigate the potential of electronic evidence in civil procedural law, as well as its drawbacks and opportunities in the digital age. To figure out what the difficulties and possibilities are in the advanced period in electronic proof as proof in common cases in court. The strategy utilized in gathering information here is utilizing auxiliary information techniques, specifically through writing concentrates on got through supporting diaries and articles. How does the Indonesian Common Technique Regulation direct electronic reports and additionally data as proof. What is the acknowledgment, legitimacy and strength of the proof in common case preliminaries to make lawful sureness for individuals looking for equity.